2017
DOI: 10.1038/s41598-017-01753-w
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Resistive Behavior and Dimensional Crossover in Disordered Superconducting TiN Films

Abstract: A reentrant temperature dependence of the normal state resistance often referred to as the N-shaped temperature dependence, is omnipresent in disordered superconductors – ranging from high-temperature cuprates to ultrathin superconducting films – that experience superconductor-to-insulator transition. Yet, despite the ubiquity of this phenomenon its origin still remains a subject of debate. Here we investigate strongly disordered superconducting TiN films and demonstrate universality of the reentrant behavior.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“…Superconductor-insulator transition (SIT) as one fascinating example of quantum phase transitions [1] has remained an active topic in recent years. The SIT could be controlled by various non-thermal tuning parameters [2], including disorder [3][4][5][6], thickness [7][8][9], magnetic field [4,7,10,11], chemical composition [12,13], carrier density [4,14], and gate voltage [15,16] in two dimensional (2D) superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Superconductor-insulator transition (SIT) as one fascinating example of quantum phase transitions [1] has remained an active topic in recent years. The SIT could be controlled by various non-thermal tuning parameters [2], including disorder [3][4][5][6], thickness [7][8][9], magnetic field [4,7,10,11], chemical composition [12,13], carrier density [4,14], and gate voltage [15,16] in two dimensional (2D) superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…We find τ 0 = 7.3 ± 0.3 × 10 −15 s. With this, we find R = 3 ± 0.05 k [from r 0 = R/(h/e 2 )], which is very close to sample's sheet resistance at room temperature R = 2.94 k . Furthermore, this value also describes the suppression of the superconducting critical temperature T c , following an expression originally proposed by Finkel'stein [37,38] (see also Appendix B). The suppression of T c is due to scattering and electron density fluctuations produced by the reduction of Coulomb screening.…”
Section: Resultsmentioning
confidence: 89%
“…We summarize some parameters obtained previously in both samples in Table I. In the Fig. 8, we provide the critical temperature versus sheet resistance in TiN films, from [38]. There, we calculated the dependence of T c using ln ( We reproduce data and model of Ref.…”
Section: Fig 5 In (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were taken on the titanium nitride (TiN) film having the thickness d = 7 nm, the sheet resistance in the normal state Ω ( σ n = 4.3⋅10 4 (Ω cm) −1 ) and the superconducting critical temperature T c = 3.06 K. The film was formed on the Si/SiO 2 substrate by the atomic layer deposition. Temperature dependence of the resistance of this film has been examined in 33 where it was shown that the film is quasi-2D in the considered temperature range. The sample was patterned into bridges 50 μ m wide and 250 μ m long.…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 99%